GC–MS and FT-IR Analysis of the Bio-Oil with Addition of Ethyl Acetate during Storage - Zhang, Le; Shen, Chenjie; Liu, Ronghou (Frontiers in Energy Research, 2014)
Different mass fractions (0%, 3%, 6%, 9%, 12%, and 15%) of ethyl acetate were added to bio-oil for improving its storage stability during storage at 40℃ for 35d. For different bio-oils during storage, physical properties were characterized and chemical components were determined by GC-MS and FT-IR. The results of properties characterization showed that, addition of ethyl acetate could instantly lower bio-oil viscosity, water content, and dramatically decrease the rate of aging. pH value of bio-oil can be instantly improved by adding ethyl acetate. GC-MS results revealed that addition of various content of ethyl acetate into bio-oil and its storage at 40℃ for 35d could both lead to disappearance of previous compounds and generation of new compounds. FT-IR results showed that addition of various content of ethyl acetate into bio-oils and its storage at 40℃ for 35d could slightly change the wavenumbers of substantial functional groups in bio-oils.